Detecting changes in the blood flow of the optic disk in patients with nonarteritic anterior ischemic optic neuropathy via optical coherence tomography–angiography - Xiao, Qing; Sun, Chuan-bin (Frontiers in Neurology, 2023)
Purpose: To observe the trend of changes in the radial peripapillary capillary (RPC) in patients with nonarteritic anterior ischemic optic neuropathy (NAION), using optical coherence tomography-angiography (OCTA) and to correlate the results with mean defect (MD), peripapillary retinal nerve fiber layer (pRNFL), and combined thickness of the macular ganglion cell complex (mGCC). Methods: This was a prospective observational study. A total of 103 patients (103 eyes) with NAION were enrolled. Whole en face image vessel density (WiVD), intra disc vessel density (id VD) and peripapillary vessel density were measured in the RPC plexus of the optic nerve head, using OCTA. The thickness of pRNFL and mGCC were measured by optical coherence tomography (OCT). The examinations were repeated at ≤ 3 weeks, 4-8 weeks, 9-12 weeks, 13-24 weeks, and >24 weeks after presentation with NAION. Results: A total of 103 affected eyes from 103 NAION patients (average age 54.71±7.93 years) were included in the study. The initial RPC WiVD was significantly reduced after the acute NAION (≤3 weeks) (F=19.404, P<0.001), and tended to be stable from the 8th week. However, there was no significant decrease in id VD between every two groups (F=1.037, P=0.389). Over the course of NAION, the superonasal (SN) RPC, superior mGCC, and superotemporal (ST)RNFL decreased with time (F=36.247, 48.812, 133.055, P<0.001). Correlations were found between S-mGCC and temporosuperior (TS) RPC in the NAION phase (R = 0.698, P<0.001), and (ST) RPC and (ST) RNFL (R=0.610, P<0.001). MD was correlated with TS RPC (R = −0.315, P<0.01) and superior mGCC (R=−0.175, P=0.010). Conclusions: Over the course of NAION, the OCTA showed a tendency for change in the retinal capillary plexus in the optic nerve. OCTA provided a practical and useful tool for the observation of papillary perfusion in NAION.